1994
DOI: 10.1002/1097-0142(19940201)73:3<605::aid-cncr2820730317>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Serum tumor markers in non-small cell lung cancer. A comparative analysis

Abstract: Background. The role of serum tumor markers in non‐small cell lung cancer (NSCLC) remains undefined. New proposed markers have seldom been rigorously compared with existing standards. The authors prospectively compared the performance of three new monoclonal antibodies (MoAb) (5E8, 5C7, and 1F10) with the established serum markers carcinoembryonic antigen (CEA) and squamous cell carcinoma antigen (SCC). Methods. The cohort consisted of 45 consecutive outpatients with newly diagnosed NSCLC. Control subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 14 publications
0
8
0
2
Order By: Relevance
“…Indeed, some studies showed a negative prognostic value for CEA 7,18 while others did not. [19][20][21] These discrepancies probably highlight the need for specific evaluation of CEA in distinct subgroups according to histology 22 or stage of disease. 17 Prognostic value of high NSE level did not reach statistical significance neither in univariate (p ¼ 0.08) nor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, some studies showed a negative prognostic value for CEA 7,18 while others did not. [19][20][21] These discrepancies probably highlight the need for specific evaluation of CEA in distinct subgroups according to histology 22 or stage of disease. 17 Prognostic value of high NSE level did not reach statistical significance neither in univariate (p ¼ 0.08) nor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 56%
“…The search for non-invasive tumor biomarkers is rapidly expanding and investigation into circulating biomarkers is the subject of intense research. Several serum tumor markers such as the carcinoembryonic antigen or Cytokeratin-21-Fragment (CYFRA 21-1) may carry some prognostic and predictive information in NSCLC, although their use is currently limited and the biochemical methodologies used to measure them are still labor-intensive [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The current tumor markers for NSCLC include carcinoembryonic antigen (CEA), soluble fragment of cytokeratin 19 (CYFRA21-1), tissue polypeptide antigen (TPA), neuron-specific enolase (NSE), carbohydrate antigen 125 (CA125), squamous cell carcinoma antigen (SCC) and some others [6][7][8][9][10]. Despite extensive studies so far, few are turned out to be useful in clinic.…”
mentioning
confidence: 99%